Ultra wideband amplifier and pulse synthesizer design - Fang, Chao (2011)
The objective of this Ph.D. dissertation is to describe the design and implementation of two key components for ultra-wideband (UWB) wireless system. The first is a high gain and low noise amplifier (LNA) for the UWB receiver. The second is a novel distributed UWB pulse synthesizer for the UWB transmitter.